Suicide Notes: Forensic Linguistic Profiling Analysis - Asep Surahman (Universitas Warmadewa, 2022)
Forensic linguistics is the branch of the linguistics study which investigates legal text in crime. The aim research is to identify the suicide notes: forensic linguistic profiling analysis. The research method used cumulative sum calculation strategy for elements: SL, Pron, Prep, Ver, Adj, Adv, Conj, CSS-SL, CSS-Pron, CSS-Prep, CSS-Ver, CSS-Adj, CSS-Adv, & CSS-Conj. The program read the given texts and counted the percentage of words that reflect different emotions, thinking styles, and social concerns. The result shows that Based on the analysis of the first letter, a graph of parallel relationships is obtained between SL and CSS-SL, Pron and CSS-Pron, Ver and CSS-Ver, Adv and CSS-Adv, and Conj and CSS-Conj. Meanwhile, there are still lines that intersect in the graph of the relationship between Prep and CSS-Prep and Adj and CSS-Adj. This indicates that the first letter is genuine, considering that the number of graphs showing parallel relationships is more dominant than those with intersecting lines.